2008
DOI: 10.1016/j.jhazmat.2008.02.105
|View full text |Cite
|
Sign up to set email alerts
|

Ferric ion mediated photochemical decomposition of perfluorooctanoic acid (PFOA) by 254nm UV light

Abstract: a b s t r a c tThe great enhancement of ferric ion on the photochemical decomposition of environmentally persistent perfluorooctanoic acid (PFOA) under 254 nm UV light was reported. In the presence of 10 M ferric ion, 47.3% of initial PFOA (48 M) was decomposed and the defluorination ratio reached 15.4% within 4 h reaction time. While the degradation and defluorination ratio greatly increased to 80.2% and 47.8%, respectively, when ferric ion concentration increased to 80 M, and the corresponding half-life was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 29 publications
3
56
1
2
Order By: Relevance
“…Results of previous studies indicated that sonochemical and photochemical degradation processes are effective to degrade PFOA [9,10]. PFOA could be completely degraded with 50 mmol$L -1 persulfate at 90°C after 4 h of microwave irradiation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Results of previous studies indicated that sonochemical and photochemical degradation processes are effective to degrade PFOA [9,10]. PFOA could be completely degraded with 50 mmol$L -1 persulfate at 90°C after 4 h of microwave irradiation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that high-frequency ultrasonication (Moriwaki et al, 2005;Vecitis et al, 2008;Panchangam et al, 2009a), microwave-induced persulfate (Lee et al, 2009(Lee et al, , 2012, electrochemical method (Guan et al, 2007;Zhuo et al, 2011), and photochemical and photocatalytic methods based on 185 nm VUV or 254 nm UV (Chen et al, 2007;Cho, 2011;Giri et al, 2011aGiri et al, , 2011bGiri et al, , 2012Li et al, 2012;PhanThi et al, 2013;Hori et al, 2004Hori et al, , 2005Dillert et al, 2007;Wang et al, 2008;Wang and Zhang, 2011;Panchangam et al, 2009b;Huang et al, 2007;Park et al, 2009) can degrade PFOA in a stepwise way. In oxidative processes, generally an electron transfers from PFOA to some excited active species, such as sulfate radical anion (SO 4 U− ) (Lee et al, 2009;Hori et al, 2005), carbonate radical anions (CO 3 U− ) (PhanThi et al, 2013), photogenerated holes (Li et al, 2012;Panchangam et al, 2009b) and PFOA complexes (Wang et al, 2008;Wang and Zhang, 2011), and then a perfluoroalkyl radical is formed after decarboxylation of PFOA.…”
Section: Introductionmentioning
confidence: 99%
“…However, ultraviolet (UV) radiation-based oxidation methods are shown to be more promising than other AOTs. Although direct UVC (254 nm) photolytic degradation of PFOA is negligibly small (Chen et al 2007;Giri et al 2011), use of chemical oxidants together with UVC can decompose the compound more easily (Chen and Zhang 2006;Wang et al 2008;Cao et al 2010;Tang et al 2012). Furthermore, it has been demonstrated during the last few years that vacuum UV (VUV) (185 nm) photolysis is more efficient than other VU-based methods for PFOA degradation (Chen et al 2007;Giri et al 2011Giri et al , 2012.…”
Section: Introductionmentioning
confidence: 99%